Lugar de mulher é na política : recrutamento e carreiras políticas em Sergipe - Santos, Vanderson de Gois (2012)
The central analytical concern was situated, more generally, on the relationship between political participation and socio-cultural resources triggered according to the underlying logic of the political game, and in a more specific level, it was interested to the research the reconstitution of symbolic elements present in what we are here calling symbolism of female political representation, constituted by the presence of women's participation in political activities in state legislative in Sergipe. To this end, it was analyzed more closely the political universe built around the activities of Goretti Reis (DEM) and the main concepts that rule this everyday actions.